Peluang dan Tantangan Sistem Pelatihan Berbasis AI dalam Meningkatkan Keterampilan Tenaga Kerja di Era Digital - Anggono, Sigit Umar; Supriyanto, Supriyanto (LPPM Universitas Sains dan Teknologi Komputer, 2025)
The rapid evolution of digital technology has reshaped workforce training paradigms, with Artificial Intelligence (AI) emerging as a transformative tool. This study investigates the opportunities and challenges of implementing AI-based training systems to enhance workforce skills in the digital era. Data were collected through surveys, in-depth interviews, and focus group discussions involving industry practitioners, AI developers, and workers. The results indicate a training effectiveness average of 70.2% (SD = 9.8) and satisfaction levels averaging 75.4% (SD = 8.5). Logistic regression analysis revealed a significant positive relationship between AI adoption and skill improvement, with a success probability of 68.9%. Despite these promising outcomes, challenges such as limited digital infrastructure, low digital literacy, and resistance to technology adoption persist, particularly in developing regions. This study provides strategic recommendations for inclusive digital transformation, emphasizing collaborative efforts between governments, private sectors, and educational institutions. These findings contribute to theoretical and practical knowledge for advancing AI-based training systems and fostering a sustainable, equitable workforce transformation.